2012
DOI: 10.1292/jvms.11-0095
|View full text |Cite
|
Sign up to set email alerts
|

Elution Profiles of Cefazolin from PMMA and Calcium Sulfate Beads Prepared from Commercial Cefazolin Formulations

Abstract: ABSTRACT. Antibiotic beads have become popular for the treatment of local bacterial infections. The preparation of antibiotic beads from commercial pharmaceutical antibiotics is a convenient method in clinic. The elution characteristics of cefazolin from polymethylmethacrylate (PMMA) (SmartSet HV, Depuy I and Cemfix 3) beads and calcium sulfate beads were studied. Commercial cefazolin formulation was incorporated in PMMA or calcium sulfate at 1 g cefazolin /10 g of matrix substances to form beads. The concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…22 Most recently, Udomkusonsri et al compared three varieties of PMMA (Cemfix, Depuy I, and SmartSet HV) with pure calcium sulfate and found that the total elution of cefazolin from calcium sulfate was greater than any of the PMMA types during the 15-day study, and the daily elution of calcium sulfate was significantly (p < 0.05) higher than the PMMA on days 1-11. 23 In addition to advancing the characterization of calcium sulfate, this report ( Figure 5) also supported our previous work that smaller beads eluted much quicker than the larger beads. 17 The clinical relevance of this difference between the elution rates of 3.0 vs. 4.8 mm beads must be further examined in an animal model.…”
Section: Discussionsupporting
confidence: 88%
“…22 Most recently, Udomkusonsri et al compared three varieties of PMMA (Cemfix, Depuy I, and SmartSet HV) with pure calcium sulfate and found that the total elution of cefazolin from calcium sulfate was greater than any of the PMMA types during the 15-day study, and the daily elution of calcium sulfate was significantly (p < 0.05) higher than the PMMA on days 1-11. 23 In addition to advancing the characterization of calcium sulfate, this report ( Figure 5) also supported our previous work that smaller beads eluted much quicker than the larger beads. 17 The clinical relevance of this difference between the elution rates of 3.0 vs. 4.8 mm beads must be further examined in an animal model.…”
Section: Discussionsupporting
confidence: 88%
“…Recent orthopedic literature has noted good clinical efficacy in the treatment of chronic osteomyelitis with bio-absorbable, antibiotic impregnated calcium sulfate beads, with no recurrent episodes of infection and a low rate of self-limiting, wound drainage. 10,11,1416 Moreover, studies have demonstrated that the concentration of antibiotic released from calcium sulfate beads was three times that of the concentration released from the PMMA beads in vitro, 18 with more consistent, prolonged levels of local antibiotic delivery. 15,16 These beads provide adequate local antibiotic levels for approximately 6–10 weeks, at which time they dissolve.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when compared, to PMMA, calcium sulfate beads have showed a better "in vitro" elution profile 17 especially when cefazolin was used as a mixed antibiotic and a better "in vitro" inhibition of bacterial growth. [25][26][27][28] The use of calcium sulfate beads is not free from complications. McPherson et al 25 reported the presence of a copious exudate from the wound requiring surgical intervention in 3.2% of patients following the use of calcium sulfate beads to treat PJI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when compared, to PMMA, calcium sulfate beads have showed a better “in vitro” elution profile 17 especially when cefazolin was used as a mixed antibiotic and a better “in vitro” inhibition of bacterial growth. 25 28…”
Section: Discussionmentioning
confidence: 99%